2016
DOI: 10.1002/14651858.cd009210.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative angiotensin-converting enzyme inhibitors or angiotensin II type 1 receptor blockers for preventing mortality and morbidity in adults

Abstract: BackgroundPerioperative hypertension requires careful management. Angiotensin-converting enzyme inhibitors (ACEIs) or angiotensin II type 1 receptor blockers (ARBs) have shown efficacy in treating hypertension associated with surgery. However, there is lack of consensus about whether they can prevent mortality and morbidity. ObjectivesTo systematically assess the benefits and harms of administration of ACEIs or ARBs perioperatively for the prevention of mortality and morbidity in adults (aged 18 years and abov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 82 publications
2
31
0
2
Order By: Relevance
“…A meta‐analysis of three randomised trials (a total of 188 patients limited to cardiac and vascular surgery) and two observational studies ( n = 434 patients undergoing various types of elective surgery) showed that administration of RAA before surgery conferred a 50% greater risk of intraoperative hypotension requiring vasopressors but no increased risk of perioperative myocardial infarction (MI) . A recent Cochrane review came to similar conclusions . An observational study on orthopaedic patients demonstrated significant increase in post‐operative acute kidney injury (AKI) after adjusting for other confounders in patients prescribed RAA .…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…A meta‐analysis of three randomised trials (a total of 188 patients limited to cardiac and vascular surgery) and two observational studies ( n = 434 patients undergoing various types of elective surgery) showed that administration of RAA before surgery conferred a 50% greater risk of intraoperative hypotension requiring vasopressors but no increased risk of perioperative myocardial infarction (MI) . A recent Cochrane review came to similar conclusions . An observational study on orthopaedic patients demonstrated significant increase in post‐operative acute kidney injury (AKI) after adjusting for other confounders in patients prescribed RAA .…”
Section: Introductionmentioning
confidence: 92%
“…5 A recent Cochrane review came to similar conclusions. 6 An observational study on orthopaedic patients demonstrated significant increase in postoperative acute kidney injury (AKI) after adjusting for other confounders in patients prescribed RAA. 7 A retrospective analysis of a large prospective cohort (n = 4802) of patients taking RAA routinely showed 18% reduction in adjusted risk of intraoperative hypotension, cardiovascular events and death in those who withheld their medication prior to surgery.…”
Section: Introductionmentioning
confidence: 99%
“…A recent Cochrane review by Zou et al . assessed the administration of preoperative ACEI or ARB in adults undergoing any type of surgery under general anaesthesia including cardiac surgery and the effect on mortality and morbidity; however, renal outcomes were not reliably reported . Several retrospective studies to determine whether long‐term use of ACEI/ARB was associated with increased incidence of AKI after cardiac surgery have found a significantly increased incidence of postoperative renal dysfunction in patients on ACEI/ARB therapy (OR 1.18, 1.36, 1.28 and 1.24) .…”
Section: Risk Factors For Cardiac Surgery‐associated Acute Kidney Injurymentioning
confidence: 99%
“…A recent Cochrane review by Zou et al assessed the administration of preoperative ACEI or ARB in adults undergoing any type of surgery under general anaesthesia including cardiac surgery and the effect on mortality and morbidity; however, renal outcomes were not reliably reported. 21 Several retrospective studies to determine whether long-term use of ACEI/ARB was associated with increased incidence of AKI after cardiac surgery have found a significantly increased incidence of postoperative renal dysfunction in patients on ACEI/ARB therapy (OR 1.18, 1.36, 1.28 and 1.24). [22][23][24] The Translational Research Investigating Biomarker Endpoints in AKI study, a prospective multicentre study of 1594 adults undergoing cardiac surgery, also reported that continued preoperative ACEI/ARB administration was associated with AKI as evidenced by greater increases in postoperative serum creatinine levels (relative risk 1.24).…”
Section: Risk Factors For Cardiac Surgery-associated Acute Kidney Injmentioning
confidence: 99%
“…In patients with chronic kidney disease (CKD) and diabetes, ACEi/ARBs are recommended by the National Institute of Health and Care Excellence, due to their renoprotective effect . In cardiac surgery, the peri‐operative administration of ACEi/ARBs has been associated with a lower‐risk of AKI . There is currently a paucity of data to support the routine continuation or withholding of ACEi/ARBs peri‐operatively in non‐cardiac surgery, with no large cohort or randomised studies examining the impact on the incidence of AKI.…”
Section: Introductionmentioning
confidence: 99%